MENINGKATKAN PURCHASE INTENTION MELALUI BRAND EQUITY DENGAN STRATEGI CO-BRANDING DAN SOCIAL MEDIA MARKETING PADA BRAND FASHION INDONESIA - Naofal, Ahmad; Wilujeng, Ita Prihatining (Universitas Gunadarma, 2024)
Local fashion products have gained the trust of the Indonesian people through the LocalPride campaign with a survey of 40.2%. Brand The aim of this research is to determine the influence of co-branding and social media marketing strategies on purchase intentions through brand equity. The difference between this study compared to previous studies is the addition of social media marketing variables and considering mediating variables which act as a link in influencing purchase intention. The type of research used was descriptive research and explanatory research with a sample of 260 Instagram followers from the local brand. The analysis technique used is descriptive statistics and PLS analysis. The results show that co-branding and social media marketing (SMM) have a direct and significant influence on purchase intention and brand equity. It was also found that brand equity has a direct influence on purchase intention. Co-branding has an indirect, positive and significant effect on purchase intention through brand equity, but social media marketing does not have an indirect effect on purchase intention through brand equity.